Active surveillance inclusion criteria under scrutiny in magnetic resonance imaging-guided prostate biopsy: a multicenter cohort study - Kornienko, Kira; Siegel, Fabian; Borkowetz, Angelika Sabina Maria; Hoffmann, Manuela Andrea; Drerup, Martin; Lieb, Verena; Bründl, Johannes; Höfner, Thomas; Cash, Hannes; Hardenberg, Jost von; Westhoff, Niklas Christian (Prostate cancer and prostatic diseases, 2022)
BACKGROUND: Although multiparametric magnetic resonance imaging (mpMRI) is recommended for primary risk stratiﬁcation and follow-up in Active Surveillance (AS), it is not part of common AS inclusion criteria. The objective was to compare AS eligibility by systematic biopsy (SB) and combined MRI-targeted (MRI-TB) and SB within real-world data using current AS guidelines. - METHODS: A retrospective multicenter study was conducted by a German prostate cancer (PCa) working group representing six tertiary referral centers and one outpatient practice. Men with PCa and at least one MRI-visible lesion according to Prostate Imaging Reporting and Data System (PI-RADS) v2 were included. Twenty different AS inclusion criteria of international guidelines were applied to calculate AS eligibility using either a SB or a combined MRI-TB and SB. Reasons for AS exclusion were assessed. - RESULTS: Of 1941 patients with PCa, per guideline, 583-1112 patients with PCa in both MRI-TB and SB were available for analysis. Using SB, a median of 22.1% (range 6.4-72.4%) were eligible for AS. Using the combined approach, a median of 15% (range 1.7-68.3%) were eligible for AS. Addition of MRI-TB led to a 32.1% reduction of suitable patients. Besides Gleason Score upgrading, the maximum number of positive cores were the most frequent exclusion criterion. Variability in MRI and biopsy protocols potentially limit the results. - CONCLUSIONS: Only a moderate number of patients with PCa can be monitored by AS to defer active treatment using current guidelines for inclusion in a real-world setting. By an additional MRI-TB, this number is markedly reduced. These results underline the need for a contemporary adjustment of AS inclusion criteria. Prostate Cancer and Prostatic Diseases (2022) 25:109-116; https://doi.org/10.1038/s41391-021-00478-2
Gesehen am 02.10.2023